Immunological response to COVID-19 and its role as a predisposing factor in invasive aspergillosis - Mahin Tavakoli; Tahereh Shokohi; Cornelia Lass-Flörl; Mohammad Taghi Hedayati; Martin Hoenigl (Mazandaran University of Medical Sciences, 2020)
The world is involved with a pandemic coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2. The clinical manifestations of reported COVID-19-associated pulmonary impairments range from asymptomatic infections to a pneumonia-induced acute respiratory distress syndrome that requires mechanical ventilation. Fungal superinfections complicating the clinical course remain underexplored. Angiotensin-converting enzyme 2, the receptor for COVID-19 that is mainly expressed in airway epithelia and lung parenchyma, is considered an important regulator of innate immunity. With regard to the viral-cell interaction, imbalanced immune regulation between protective and altered responses caused by the exacerbation of inflammatory responses should be considered a major contributor to secondary pulmonary aspergillosis. In addition, the complex inherited factors, age-related changes, and lifestyle may also affect immune responses. The complication and persistence of invasive aspergillosis have been well described in patients with severe influenza or COVID-19. However, there is a scarcity of information about the immunological mechanisms predisposing patients with COVID-19 to fungal co-infections. Therefore, this study was conducted to investigate the aforementioned domain.